Carcass characteristics and meat quality of Aberdeen Angus steers finished on different pastures - Devincenzi,Thais (2012)
The present study was conducted to assess carcass features, physicochemical and sensory parameters of meat from steers finished on three types of pastures: natural pasture; natural pasture improved, fertilized and oversown with winter species; and annual summer grassland. The experiment was conducted from December 14, 2009 to November 30, 2010, with treatments distributed in a completely randomized design with a different number of replicates. Animals were used as experimental units. Experimental animals were Aberdeen Angus steers with twenty months of initial age and 354±27.4 kg of live weight, on average. The highest average daily gains were obtained for the annual summer grassland. There was no effect of treatments on carcass conformation. The highest carcass yield was obtained on the improved natural pasture. Forequarter yield, side cut yield and longissimus muscle area were similar between the pastures. Moisture and total lipids were not affected by the pasture. Thawing and cooking losses were higher in improved natural pasture and lower in sorghum pasture. Regardless of the treatment, the meat had luminosity ranging from intermediate to dark, high in red, high in yellow, and considered within the normal range for beef. Meat of higher shear force was found in natural pasture, and lower shear force was observed in meat from annual summer grassland. Average live weight daily gain explained 18% of the shear force. Sensory evaluation by duo-trio test showed differences between samples from distinct pastures in flavor. All the studied systems allow for desirable characteristics in carcass and meat.